Črno na belem - fehéren feketén. Pomenske razsežnosti črne in bele barve v slovenski in madžarski frazeologiji - Bernjak, Elizabeta (Slavistična revija, 2007)
The article presents the semantic implications of the colours black and white in Slovene and Hungarian phraseology from a cognitive aspect, the symbolic and metaphoric role of the black and white colour in the conceptualization of abstract domains and their language (praseological) realization. Symbols and metaphors aren't linguistic signs, but also the components of mental processes, which are more or less universal and this fact is being reflected in the high level of convergence between the phraseological units containing colours in the observed languages.
Keywords: črna in bela barva; frazem; frazeologija; Hungarian language; iconicity; ikoničnost; madžarščina; metaforika; metaphor; phraseological unit; phraseology; simbolika; Slovene language; slovenščina; symbolism; the colours black and white